Henri Cartier-Bresson: The decisive moment. - Cartier-Bresson, Henri, 1908-; Scholastic Magazines, inc.; Scholastic Book Services (Scholastic Magazines in cooperation with International Fund for Concerned Photography. Released by Scholastic Book Services, 1973)
Photographer Henri Cartier-Bresson uses photographs of people in France and other countries to express his views on life, man, and the world in which he lives.
Library's copy has 73 slides.
With teaching guide.
Editor, Sheila Turner; coordinator, Cornell Capa.
Keywords: Cartier-Bresson, Henri, -- 1908-; Photography, Artistic